Chemical process safety : learning from case histories - Sanders, R. E. (Roy E.) (Elsevier Butterworth Heinemann, 2005)
Gives insight into eliminating specific classes of hazards, while providing real case histories with valuable messages. There are practical sections on mechanical integrity, management of change, and incident investigation programs, along with a long list of helpful resources. New chapter in this edition covers accidents involving compressors, hoses and pumps. * Stay up to date on all the latest OSHA requirements, including the OSHA required Management of Change, Mechanical Integrity and Incident Investigation regulations. * Learn how to eliminate hazards in the design, operation and maintenance of chemical process plants & petroleum refineries. * World-renowned expert in process safety, Roy Sanders, shows you how to reduce risks in your plant. * Learn from the mistakes of others, so that your plant doesn't suffer the same fate. * Save lives, reduce loss, by following the principles outlined in this must-have text for process safety. There is no other book like it!